2015
DOI: 10.1177/230949901502300223
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation for the Disrupted Acromioclavicular Joint Using a Braided Polyester Prosthetic Ligament

Abstract: Purpose. To report outcomes of 21 men who underwent stabilisation for the disrupted acromioclavicular joint (ACJ) using a braided polyester prosthetic ligament. Methods. 21 men aged 23 to 76 (mean, 43) years underwent stabilisation for the disrupted ACJ of Rockwood type 3 (n=12), type 4 (n=1), and type 5 (n=8) using a braided polyester prosthetic ligament. Results. The mean time from injury to surgery was 6.8 (range, 0-19) months. The mean follow-up duration was 30 (range, 7-67) months. The mean Constant Score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…Rest all 25 patients returned to their pre-injury level of function at a mean of 6 months. The mean Oxford Shoulder Score and results in our study are similar or even better to the recent newer techniques [34,35] . Moreover surgical management of ACJ dislocation using modified Weaver-Dunn procedure does not require costly and sophisticated instruments and can be done easily in any basic surgical setup even in rural area with limited availability of resources.…”
Section: Discussionsupporting
confidence: 82%
“…Rest all 25 patients returned to their pre-injury level of function at a mean of 6 months. The mean Oxford Shoulder Score and results in our study are similar or even better to the recent newer techniques [34,35] . Moreover surgical management of ACJ dislocation using modified Weaver-Dunn procedure does not require costly and sophisticated instruments and can be done easily in any basic surgical setup even in rural area with limited availability of resources.…”
Section: Discussionsupporting
confidence: 82%
“…Wright et al reported high satisfaction rates (20/ 21). 37 Mean abduction power of operated site was 82% of the normal. There was no infection, clavicular or coracoid fracture and none of the patient required implant removal.…”
Section: Surgilig™ Reconstructionmentioning
confidence: 89%
“…This can be performed as an isolated procedure, or as part of a more complex procedure for treatment of AC joint injuries. Distal clavicle excision generally results in good to excellent outcomes and has been used in several studies as an additional procedure for the reduction of the dislocated clavicle [ 26 , 49 ], but no definite conclusions can be drawn regarding the role distal clavicle excision might play in AC joint stabilization postoperatively.…”
Section: Discussionmentioning
confidence: 99%